House of Entrepreneurship, as a mechanism to activate the idea of establishing small and medium enterprises among universities students - House of Entrepreneurship at Constantine University model - - Benjamaa, Amina; Jarman, Rbii (Milev Journal of Research and Studies, 2017)
The purpose of this study is to understand the role of the House of Entrepreneurship in activating the idea of establishing small and medium institutions among universities students, After the university graduate was looking for a job, he became the one who creates and provides jobs. This is achieved by integrating and linking the culture of entrepreneurship with higher education programs, through which he can acquire various skills (professional, technical, managerial and personal), attitudes and behaviors, And the development of the entrepreneurial spirit, which carries with it the spirit of initiative and risk, and the culture of selfemployment ..., which is developed and valued through the support programs that are created at the level of the university as the House of Entrepreneurship, and the study concluded that the House of Contractors contribute to enable students to enter Business world through providing training courses and business consultations and providing an integrated business environment that helps them achieve and sustain their projects.